EEKTIITAS MODEL PEMELAJARAN KOOPERATI TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS SISA - Dian Dharma (Jurnal Edukasi dan Penelitian Matematika, 2018)
The understanding of mathematical concept has a very important role in achieving the learning objectives, because it’s a basic ability to be owned by students. The understanding of mathematical conceptshould be developed in learning process. However, mathematics learning that occurred in the class XI IPS SMA Pembangunan Laboratorium UNP Padang does not optimally to facilitate students in the process to find the concepts. The purpose of this research is to figure out whetherthe understanding of mathematical concept ofstudent who have been taught using cooperative learning model type STAD is better than using conventional model in class XI IPS SMA Pembangunan Laboratorium UNP Padang. The type of this research is quasy experiment with design is Static Group Design. Data were collected by using test of understanding of mathematical concept. Data were analyzed by using Mann-Whitney test. Based of the data analysis, it can be concluded that student’s understanding of mathematical concept who have been taught using cooperative learning model type STAD is better than using conventional model in class XI IPS SMA Pembangunan Laboratorium UNP Padang.  Keywords – cooperative learning, STAD, Student Teams Achievement Divisions, understanding of mathematical concepts